"THE EFFECT OF FINANCIAL PERFORMANCE ON STOCK PRICE (A Study on Automotive Company Enlisted in Bursa Efek Indonesia (BEI) on 2009-2011)â€ - Farahdita, Ines; sabirin, M. Tojibus (Jurnal Ilmiah Mahasiswa FEB, 2012)
This study aims to determine the effect of the financial performance on the stock price of automotive company. This study use a purposive sampling method as the sampling method from all companies listed on the Stock Exchange in the year 2009-2011. The dependent variable of this research is the stock price, while its independent variable is the Earning Per Share (EPS), Debt to Equity Ratio (DER), Net Profit Margin (NPM), the Current Ratio (CR) and Price Earning Ratio (PER). Data analysis was performed by using multiple regression analysis. The t test result showed that, Earning Per Share (EPS), Current Ratio (CR), Price Earning Ratio (PER) have a significant effect on stock prices, while the Debt to Equity Ratio (DER) and ) Net Profit Margin (NPM) has no significant effect on the stock prices. Keywords: Earning Per Share (EPS), Debt to Equity Ratio (DER), Net Profit Margin (NPM), the Current Ratio (CR) and Price Earning Ratio (PER) and the stock price.